The Effect of Social Capital and Collaborative Knowledge Creation on E-Business Proactiveness and Organizational Agility in Creating Business Sustainability - Erland Perdana; Tantri Yanuar Rahmat Syah (Jurnal Internasional Penelitian Bisnis Terapan, 2023)
Social capital is significant for an organization while collaborative knowledge creation and e-business proactiveness support the organization in every business process. This research intends to identify social capital and collaborative knowledge creation in influencing e-business proactiveness and organizational agility in order to obtain business sustainability. This research was conducted in three months on 24 companies from the Financial Services Industry (FSI) sector in Greater Jakarta, Indonesia, involving 155 respondents. The data was analyzed using the SEM-PLS. The results confirm that social capital positively impacts e-business proactiveness and collaborative knowledge creation in the FSI sector. Besides, e-business proactiveness and collaborative knowledge creation demonstrate a positive influence on the FSI’s organizational agility. Then, organizational agility significantly impacts business sustainability, while e-business proactiveness has yet to be proven to increase business sustainability in the FSI sector. The managerial implications of this research can be applied by organizations in developing social capital through social networks such as business partners in order to improve other aspects in creating business sustainability.